ANALISA POTENSI PENINGKATAN KINERJA HHP BOILER BERDASARKAN PRINSIP NERACA PANAS - I Ketut Warsa; Yuniarti Yuniarti; Eka Megawati (Sekolah Tinggi Teknologi MIGAS, 2021)
The boiler is in charge of generating steam. The steam produced can be used for several purposes, among others: as a working fluid to drive steam engines such as turbine engines and compressor piston engines, as a heating medium for heating liquids so that they are always at a set temperature, as an auxiliary medium for processing and so on. . In the context of energy conservation today, energy use is very much taken into account, because energy consumption is closely related to operating costs. In principle, the more energy consumed means higher operating costs. For energy savings, it is expected that fuel consumption in the operation of the HHP Boiler is as optimal as possible, so as to provide the appropriate heat. To find out the above, it is necessary to calculate the performance of the boiler. In this case the compilers use the Heat Loss method with dual fuel (fuel oil and fuel gas). From the evaluation results of the HHP Boiler with a heat balance, the efficiency is 89.53%.